The Dynamics Of The Socio-Economic Life Of Female Heads Of Households In Popaya Village, Dengilo Sub-District, Pohuwato District - Moko, Mey Yulan; Juramang, Risnayanti R; Bantui, Adriani (Jambura Journal Civic Education, 2024)
The Papaya Village Government annually collects population data to identify its community's socio-economic needs. From the results of preliminary observations, it was found that in Popaya Village, there are 20 female heads of families who are included as socio-economically vulnerable women and have the responsibility to fulfill the needs of their families. This study aims to determine the dynamics of the socio-economic life of female heads of households in Popaya Village, Dengilo Sub-district, Pohuwato Regency, and the impacts of being a female head of household. The qualitative research method is a method used to research natural object conditions. The results showed that the dynamics of the socio-economic life of women's family heads in Popaya Village are diverse. Regarding role changes, women's family heads must carry out dual roles: breadwinners and homemakers. Meanwhile, in terms of changes in thinking patterns, it can be seen that after becoming the head of the household, the female head of the room must try to think about generating income to meet family needs, whether it is becoming a farm laborer, cleaning houses and schools, or establishing micro, small, and medium enterprises. Being the head of the family significantly impacts the lives of women heads of households; it is difficult to get a job, and economic limitations are caused by low education and age, causing women heads of families to live in economic limitations.